Main Characteristics and Space Structure of a Moving Industrial Robot - R. Siddikov; M. Amanbayev (Research Parks Publishing LLC, 2021)
The article describes a number of characteristics of the industrial robot (IR) in the implementation of spatial manipulation operations, namely, the robot's working space, work area, geometric characteristics, coordinate system, the degree of mobility in the process. An IR with six or more links is a complex technical system. Therefore, according to the real construction of the IR, six or fewer links are involved in the technological process. The smaller the number of links, the simpler the control of the robot.